Animal ethics committees of veterinary schools in Turkey - Yasar, A.; Ozturk, R.; Ozen, A. (Indian Veterinary Journal, 2006)
The first known ethics committee in the world was formed in 1965 in Karolinska Hospital. After this date, especially after 1970s, ethics committees have spread over the world rapidly. Ethics committees have become a current issue in Turkey in the 1980s and the first ethics committee was established in 1986 in Hacettepe Medical School (Yasar, 2003). Ethics Committee concept in the field of veterinary medicine took place for the first time in Veterinary Medicine Deontology Regulation legislated and published on the Official Gazette on July 9, 1994 (Anonymous, 1994). After this date, ethics committees have begun to be formed in veterinary schools. The purpose of this study was to evaluate the animal ethics committees in the veterinary schools in Turkey.